EFFECTS OF UREA AND ORGANIC FERTILIZER TREATMENTS ON OIL PALM (ELAEIS GUINEENSIS JACQ.) SEEDLING GROWTH IN THE PRE-NURSERY - Sirait, Bilter A.; Bondar, Benito; Simatupang, Uli C.; Manurung, Agnes Imelda (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2025)
The purpose of this study was to determine the effect of urea fertilizer and organic manure derived from goat manure on the growth of oil palm seedlings in the pre-nursery stage. The research was conducted using a factorial Randomized Complete Block Design (RCBD) consisting of two factors. The first factor was urea fertilizer treatment with three levels: U0 = control, U1 = 3 g/polybag, and U2 = 6 g/polybag. The second factor was the dose of goat manure (K) with three levels: K1 = control, K2 = 200 g/polybag, and K3 = 400 g/polybag. The interaction between urea and goat manure doses had a significant effect on plant height, stem diameter, number of leaves, leaf length, leaf width, and leaf area.